Disciplinary Levels of Student Volleyball Athletes - Sahabuddin Sahabuddin; Hikmad Hakim; Syahruddin Syahruddin; Davi Sofyan (Indonesian Journal of Sport Management, 2023)
Discipline aims to train athletes to show the values of obedience, loyalty, and order, which lead to ideals and cannot be separated from the influence of their family, who always supports them. Disciplined attitudes are not only possessed by athletes but by all professions, and everyone, especially coaches, who are good examples of training, must be disciplined. Disciplined behavior will not grow but requires self-awareness, training, habits, and punishment for athletes who violate it. Discipline arises from the need to strike a balance between what an individual wants to do and what other individuals want to do. This balance is met until certain time limits. This research aims to determine The level of discipline of BKMF Volleyball FIKK UNM athletes. The population of this research is all BKMF Volleyball FIKK UNM athletes who participate in volleyball activities, with a research sample of 30 athletes selected as a saturated sample or total population. The data analysis techniques used are descriptive, data normality, and categorization using the SPSS program. Based on the results of data analysis, this research concludes that The level of discipline of BKMF Volleyball FIKK UNM athletes is in the Discipline Category.